2008
DOI: 10.1158/1078-0432.ccr-08-0109
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of GTI-2040, an Antisense to Ribonucleotide Reductase, in Combination with High-Dose Cytarabine in Patients with Acute Myeloid Leukemia

Abstract: Purpose: Inhibition of ribonucleotide reductase reduces the availability of the endogenous pool of deoxycytidine and may increase cytarabine (AraC) cytotoxicity. We performed a phase I dose escalation trial of AraC combined with GTI-2040, a 20-mer antisense oligonucleotide shown in preclinical studies to decrease levels of the R2 subunit of ribonucleotide reductase, to determine the maximum tolerated dose in adults with relapsed/refractory acute myeloid leukemia. Experimental Design: Twenty-three adults (ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 30 publications
1
42
2
Order By: Relevance
“…Detailed clinical pharmacokinetics of GTI 2040 in AML patients have been published recently (Klisovic et al, 2008).…”
Section: Enzyme Kinetics Of An Antisense Drug Gti-2040mentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed clinical pharmacokinetics of GTI 2040 in AML patients have been published recently (Klisovic et al, 2008).…”
Section: Enzyme Kinetics Of An Antisense Drug Gti-2040mentioning
confidence: 99%
“…Additionally, clinically GTI-2040 is used as a 6-day infusion, and the total steady-state concentrations are in the range of 0.3 M (Klisovic et al, 2008), further justifying the use of the apparent Michaelis-Menten kinetics to describe the GTI-2040 data for approximation of the HLM enzyme kinetics, which yielded the kinetic parameter as shown in Table 2. Notably, the K m value was determined to be 6.33 M, using the unbound substrate concentrations, and this value is greater than both K d values of GTI-2040 in HLMs.…”
Section: Enzyme Kinetics Of An Antisense Drug Gti-2040mentioning
confidence: 99%
See 2 more Smart Citations
“…1). Based on this rationale, a phase I study of GTI-2040 in combination with Ara-C for the treatment of acute myeloid leukemia (AML) was carried out at this institution (14). This study has demonstrated that GTI-2040 and Ara-C can be safely given to AML patients (10).…”
Section: Introductionmentioning
confidence: 99%